CEE 5403 Lecture 6
CEE 5403 Lecture 6
CEE 5403 Lecture 6
PROCESS
CONTROL
NON INTERACTING /INTERACTING TANKS
TRANSFER PROCESS DYNAMICS
FUNCTIONS
G(S)
PROCESS DYNAMICS
PROCESS DYNAMICS
TODAY QUIZ
1. Below is an ODE of a process model Time: 30 mins
𝒅𝒙
− 𝟒𝒙 = 𝑪𝒐𝒔 𝒕
𝒅𝒕
i. Obtain Laplace Transform (LT) of the ODE.
ii. What is the order of the LT obtained?
iii. State clearly the gain K and the time constant 𝝉 of the LT obtained.
iv. Derive response of ODE in time domain, X(t).
v. Comment on your X(t) response obtained.
PROCESS DYNAMICS
𝐴2 𝑑ℎ2
= 𝑞1 − 𝑞2 𝐸𝑞 2
𝑑𝑡
PROCESS DYNAMICS
𝐴1 𝑑ℎ1 ℎ1
= 𝑞𝑖 − 𝐸𝑞 3
𝑑𝑡 𝑅1
𝐴2 𝑑ℎ2 ℎ2
= 𝑞1 − 𝐸𝑞 4
𝑑𝑡 𝑅2
At steady state….
𝐴1 𝑑ℎ1 𝐴2 𝑑ℎ2
and =0
𝑑𝑡 𝑑𝑡
ℎ1
0 = 𝑞𝑖 − 𝐸𝑞 5
𝑅1
ℎ2
0 = 𝑞1 − 𝐸𝑞 6
𝑅2
Deviation variable introduced.
PROCESS DYNAMICS
𝐻2 (𝑠) 𝑅2
= 𝐸𝑞 8
𝑄1 (𝑠) 𝐴2 𝑅2 𝑠 + 1
𝑄𝑖 (𝑠)
=?
𝑄2 (𝑠)
This we lead us to the block diagram
PROCESS DYNAMICS
𝑄2 (𝑠) 1 𝜏2 = 𝐴2 𝑅2
= 𝐸𝑞 10
𝑄𝑖 (𝑠) (𝐴1 𝑅1 𝑠 + 1)(𝐴2 𝑅2 𝑠 + 1)
𝑄2 (𝑠) 1
= 𝐸𝑞 11
𝑄𝑖 (𝑠) (𝜏1 𝑠 + 1)(𝜏2 𝑠 + 1)
PROCESS DYNAMICS
𝑑ℎ2
𝐴2 = 𝑞1 − 𝑞2 𝐸𝑞 2
𝑑𝑡
ℎ
R, resistance to flow 𝑅 =
𝑞
1
𝑞1 = (ℎ − ℎ2 )
𝑅1 1
ℎ2
𝑞2 =
𝑅2
PROCESS DYNAMICS
𝐻1 = ℎ1 − ℎ1𝑠 ; 𝐻2 = ℎ2 − ℎ2𝑠
𝑑 1 1 ℎ2 − ℎ2𝑠
𝐴2 ℎ2 − ℎ2𝑠 = ℎ1 − ℎ1𝑠 − ℎ2 − ℎ2𝑠 − 𝐸𝑞 7
𝑑𝑡 𝑅1 𝑅1 𝑅2
𝑑 1 1 𝐻2
𝐴2 𝐻2 = 𝐻1 − 𝐻2 − 𝐸𝑞 8
𝑑𝑡 𝑅1 𝑅1 𝑅2
1 1 1
𝐴2 𝑠𝐻2 𝑠 = 𝐻1 𝑠 − 𝐻2 𝑠 − 𝐻 𝑠 𝐸𝑞 9
𝑅1 𝑅1 𝑅2 2
1 1 1
𝐻2 𝑠 𝐴2 𝑠 + + = 𝐻1 𝑠 𝐸𝑞 𝐸𝑞 10
𝑅1 𝑅2 𝑅1
PROCESS DYNAMICS
𝑑 1 1
𝐴1 ℎ − ℎ1𝑠 = 𝑞 𝑡 − ℎ − ℎ1𝑠 − ℎ − ℎ2𝑠
𝑑𝑡 1 𝑅1 1 𝑅1 2
𝑑 1 1
𝐴1 𝐻1 = 𝑞 𝑡 − 𝐻1 − 𝐻2
𝑑𝑡 𝑅1 𝑅1
1 1
𝐴1 𝑠𝐻1 (𝑠) = 𝑄 𝑡 (𝑠) − 𝐻1 (𝑠) − 𝐻2 (𝑠)
𝑅1 𝑅1
𝐻1 𝑠 − 𝐻2 𝑠 𝐻1 𝑠 − 𝐻2 𝑠
𝐴1 𝑠𝐻1 𝑠 = 𝑄 𝑡 𝑠 − 𝑜𝑟 𝑄 𝑡 𝑠 = 𝐴1 𝑠𝐻1 𝑠 + 𝐸𝑞 11
𝑅1 𝑅1
PROCESS DYNAMICS
𝐴1 𝑅1 𝑠𝐻1 𝑠 = 𝑅1 𝑄 𝑡 𝑠 − 𝐻1 𝑠 − 𝐻2 𝑠 𝐸𝑞 12
𝑅1
𝐻1 𝑠 = 𝐴 𝑅 𝑠 + 1 𝐻2 𝑠 + 𝐻2 𝑠 𝐸𝑞 14
𝑅2 2 2
PROCESS DYNAMICS
𝐴2 𝑅2 𝑠 + 1 𝑅1
𝑄 𝑡 𝑠 = 𝐻2 𝑠 + 𝐴 𝑅 𝑠 + 1 𝐴1 𝑠 + 𝐴1 𝑠
𝑅2 𝑅2 2 2
𝐴2 𝑅2 𝑠 + 1 + 𝑅1 𝐴1 𝑠 𝐴2 𝑅2 𝑠 + 1 + 𝐴1 𝑅2 𝑠
𝑄 𝑡 𝑠 = 𝐻2 𝑠
𝑅2
𝐻2 𝑠 𝑅2
= 𝑙𝑒𝑡 𝜏1 = 𝐴1 𝑅1 𝑎𝑛𝑑 𝜏2 = 𝐴2 𝑅2
𝑄 𝑡 𝑠 𝐴2 𝑅2 𝑠 + 1 + 𝐴1 𝑅1 𝑠 𝐴2 𝑅2 𝑠 + 1 + 𝐴1 𝑅2 𝑠
𝐻2 𝑠 𝑅2
=
𝑄 𝑡 𝑠 𝜏2 𝑠 + 1 + 𝜏1 𝑠 𝜏2 𝑠 + 1 + 𝐴1 𝑅2 𝑠
PROCESS DYNAMICS
𝐻2 𝑠 𝑅2
𝜏1 = 𝐴1 𝑅1
=
𝑄 𝑡 𝑠 𝜏1 𝜏2 𝑠 2 + 𝑠(𝜏1 + 𝜏2 +𝐴1 𝑅2 ) + 1
𝜏2 = 𝐴2 𝑅2
𝐻2 𝑠 𝑅2
𝐺 𝑠 = =
𝑄 𝑡 𝑠 𝜏1 𝜏2 𝑠 2 + 𝑠(𝜏1 + 𝜏2 +𝐴1 𝑅2 ) + 1